The Role of Women's Leadership on the Effectiveness of Villages owned Enterprises in Indonesia - Lestari, Tyastuti Sri; Ismaniah, Ismaniah; Saimima, Ika Dewi Sartika; Nuraida, Tia (Jurnal Manajemen Pelayanan Publik, 2025)
The population of Indonesia according to the Central Statistics Agency (BPS) in mid 2023 is 278 million people. In spite of this, women still need to make up ground in a number of developmental fields, impacting national productivity. Globally, women face similar challenges in development, prompting the United Nations to prioritize sustainable development goals (SDGs) and strive for gender equality by 2030. This research is based on the theory of transformational leadership, where transformational female leaders empower villages, create inclusivity, and advance sustainable economics Leadership issues, particularly concerning women, remain a pertinent topic. In Indonesia, where women's participation in culture is limited, the Village-Owned Enterprises (BUMDes) program emerged as a pivotal initiative by the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration. BUMDes, which was established in 2014, aims to enhance community welfare by establishing legal entities managed by villages. With an important focus on women's leadership, the program has acquired prominence and has contributed significantly to the success of BUMDes, as well as to the acceleration of village towards autonomy the nation.